Teaching later British literature : a thematic approach - Pionke, Albert D., 1974- (London : Anthem Press, 2019)
Designed for both first-time teachers of survey courses in later British literature and more experienced instructors seeking a new way to approach familiar material, 'A Handbook to Teaching Later British Literature' presents a synthetic and adaptable framework for guiding students through British literary history from the 1780s through the 1940s.
II. Factory Reform through PoetryIII. The Condition of England as "Melancholy Madness"; IV. Medievalism as a Response to Industrialization; Chapter 12 Theme Five: Empire; I. Thematic Introduction; II. "To strive, to seek, to find, and not to yield"; III. National Chauvinism in "The Englishman"; IV. Of Markets and Goblins; V. Mirrors of Empire in "The Man Who Would Be King"; Schedule of Readings; Suggestions for Further Reading; Part III English Modernism; Chapter 13 Introduction; I. Periodizing the Moderns; II. Historicizing the Moderns; III. Canonizing the Moderns
Print version record.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 3, 2019).
JSTOR
Keywords: British literature -- Study and teaching; Littérature britannique -- Étude et enseignement; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LANGUAGE ARTS & DISCIPLINES -- Study & Teaching